2010
DOI: 10.1177/1077546309353365
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tracker for a Class of Sampled-data Nonlinear Systems

Abstract: In this paper, a novel observer/Kalman filter identification (OKID) based iterative learning control (ILC) for a class sample-data nonlinear system is proposed and supplies a good tracking performance in both the transient and steady-state phase. The proposed observer-based digital redesign tracker can suppress the uncertainties and the nonlinear perturbations. First, even without resetting the identical initial condition the optimal linear model of the analog nonlinear system is constructed at the operating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…). It is well known that the high-gain property can suppress system uncertainties [31]. For this reason, the high-gain property is adopted in this paper.…”
Section: Remark 1 ([31]mentioning
confidence: 99%
“…). It is well known that the high-gain property can suppress system uncertainties [31]. For this reason, the high-gain property is adopted in this paper.…”
Section: Remark 1 ([31]mentioning
confidence: 99%
“…28 Tsai et al suggested a novel observer/Kalman filter identification (OKID)–based ILC, implemented on a non-linear system, and the findings show good tracking performance. 29 Theoretically, the ILC is capable of adjusting the control signal by using the experience of previous trials. The performance error closes into the zero target e k 0 as time approaches infinity t .…”
Section: Design Of Controllermentioning
confidence: 99%
“…This result was subsequently extended to the eigensystem realization algorithm (ERA) (Juang and Pappa, 1986). The observer/Kalman filter identification (OKID) method (Juang et al, 1993;Juang, 1994) is a valuable tool for model linearization, which has been proved very effective in various difficult identification problems (Marco, 2008;Tsai et al, 2009). In this paper, modeling of decentralized low-order linear observers for a class of unknown interconnected large-scale sampled-data nonlinear systems is proposed.…”
Section: Introductionmentioning
confidence: 99%